ANALYSIS OF INTERNET DATA CUSTOMER DISRUPTION SERVICES TARGET COMPLETION TIME AT THE BUSINESS GOVERMENT ENTERPRISE & WIFI OPERATION UNIT PT. TELECOMMUNICATIONS INDONESIA. TBK (PERSERO) AREA OF NORTH SUMATRA - Satria Sitorus; Meilita Tryana Sembiring; Nazaruddin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The development of technology and information that continues to occur very rapidly around the world has resulted in developments in the use of the internet in the world. The internet connects one person to another, provides information, as a means of entertainment, as well as a means of communication. Currently, the internet has become a part of human life where it has become a basic need in addition to the need for food, clothing and shelter. The internet, which knows no space and time boundaries, has provided various conveniences for human life in carrying out daily activities, which has led to a high number of internet users in Indonesia.